Device clinical trials: the importance of “repurposing” technology - Gillaspie, Erin A. (Video-Assisted Thoracic Surgery; Vol 3 (April 2018): Video-Assisted Thoracic Surgery, 2018)
As we all know, the US is facing a cost crisis in healthcare. As a share of the nation’s gross domestic product, healthcare accounted for 17.9% in 2016 as reported in the National Health Expenditure Data from the Centers for Medicare and Medicaid Services (1). Health care economists project that this will continue to increase on an annual basis. Cost containment is essential; but what is really driving these expenditures?